DEGREE OF ANXIETY FOR COVID-19 SURVIVORS AT SANGLAH HOSPITAL DENPASAR - Silvia Ni Nyoman Sintari; Kiki Rizki Fista Andriana; Yunus Adi Wijaya (Unit Penelitian dan Pengabdian Kepada Masyarakat, STIKES Dirgahayu Samarinda, 2022)
During the current COVID_19 pandemic, patients treated in isolation rooms are required to undergo treatment separately from their families and are regularly monitored by medical officers. The survivors of COVID_19 were brought together in a tight situation guarded by health workers. Causes direct communication deficits, symptoms of depression, and anxiety in patients.. This study aims to determine the degree of anxiety in COVID_19 survivors at Sanglah Hospital Denpasar. This study uses a quantitative descriptive design with an observational descriptive approach. The research sample uses the consecutive sampling technique. The data collection instrument to measure the patient's level of anxiety is the DASS anxiety questionnaire. The results obtained from 54 respondents mostly experienced moderate anxiety, as many as 37 people (68.5%). Women of productive age are more prone to anxiety than men because they use emotional feelings more often in dealing with various things. Health workers can provide facilities and create situations that can help patients by increasing a sense of comfort and calm so that anxiety responses can be minimized and prevented.